Tapping of pili (Canarium overtime Engl.) for sustained resin yield - Ella, Arsenio B.; Domingo, Emmanuel P.; Garcia, Esteven D. (2011)
This study is a combination of..
Keywords: Pili farming; Rain and rainfall